INTRODUCTION TO VOLUME 6 : 2008 - Hashim, Norliza (PLANNING MALAYSIA, 2016)
Safety of our cities is now a global concern as more than half of the world’s population is now urban dwellers. Crime in cities is also increasing and even if we have the best police force in the country, it is still not possible for one organization to address the many factors that contribute towards crime which has influence perceptions of safety in our city. Crime in cities dictates on choice of where to live, work, shop and play and in some cities it has brought about segregation of communities, where wealthier communities that can afford security lives in gated and guarded neighbourhood. A Safe City is a sustainable city, where communities can live in a more inclusive and secure environment Root causes of crime is linked to and integrated with other issues like economics, health, housing, and the interaction of different social groups. Addressing safety issues will make cities more attractive and livable. That is why the Malaysian Institute of Planners decided to focus on the issue of Safe City in this journal’s publication. The Institute strongly feels that town planners have a role to play in making our urban spaces safer. Several articles in this journal explore the various issues that can contribute towards a Safe City and I would like to thank all the writers and editors for this special publication. Thank you.